Enhanced H-H binding and consequent H-aggregation around dislocation in α-Fe lattice. (17th June 2020) - Cui, Yanguang; Hu, Chuanzhu; Yu, Ping; Xie, Dongyue; Kong, Lingti; Rong, Yonghua; Wen, Mao; Zou, Jianxin
Abstract: H-H binding energies in tetragonal and octahedral sites (TS & OS) of α -Fe lattice were calculated by density functional theory (DFT) under correction of elastic energy. Strong attractive interactions were identified as H atoms were incorporated in 3rd and 4th nearest OS neighbors. OS-type H-aggregated clusters with binding energies exceeding 200 meV were identified. Monte Carlo simulation of H-loading indicates abnormal H-aggregation behavior around a 1/2[111] ( 10 1 ̄ ) edge dislocation in relation with the enhanced H-H binding specifically in OS of α -Fe lattice.